2021
DOI: 10.1177/17085381211039939
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative high lymphocyte-to-monocyte ratio is associated with intraoperative type I endoleak in patients with TAA with TEVAR

Abstract: Objectives Various inflammatory factors are closely associated with the incidence of thoracic aortic aneurysms (TAAs). Furthermore, the severity of inflammation is closely related to the absolute value and proportion of each leukocyte subgroup. Only few reports have analyzed the importance of lymphocyte–monocyte ratio (LMR) as a potential inflammatory marker in vascular diseases. Therefore, we aimed to investigate the effect of peripheral blood LMR on thoracic endovascular aortic repair (TEVAR) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In vascular disorders, the LMR is related to the severity of coronary artery disease [ 33 ]. Xie et al [ 34 ] suggested that a low LMR indicates a greater inflammatory response in the aortic wall, and that patients with thoracic aortic aneurysms with a high LMR are more likely to have type I endoleak during thoracic endovascular aortic repair. The present study showed that there was an association between detected bacteria and inflammation in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular disorders, the LMR is related to the severity of coronary artery disease [ 33 ]. Xie et al [ 34 ] suggested that a low LMR indicates a greater inflammatory response in the aortic wall, and that patients with thoracic aortic aneurysms with a high LMR are more likely to have type I endoleak during thoracic endovascular aortic repair. The present study showed that there was an association between detected bacteria and inflammation in the blood.…”
Section: Discussionmentioning
confidence: 99%